Structural characterization and dielectrical properties of Ag-doped nano-strontium apatite particles produced by hydrothermal method - Gurgenc, Turan (Elsevier, 2021)
In present study, pure and silver (Ag) doped nano-strontium apatite particles were produced by hydrothermal method at 180 degrees C for 12 h. The synthesized apatite particles structural characterization was carried out with X-Ray diffraction (XRD), Fourier transform infrared spectrometry (FT-IR), field emission scanning electron microscope (FE-SEM) and energy-dispersive X-ray spectrometry (EDS). The dielectrical properties of synthesized apatite particles were investigated in detail. The pure and Ag-doped strontium apatite particles were successfully synthesized by hydrothermal method. The diffraction peaks of (002) and (300) planes were shifted to lower 2 theta values with increasing the Ag doping ratio. The lattice parameters and volumes of unit cells were increased with increasing the Ag doping ratio. The size of the particles is in nanoscale range and nano-rod like form. The (Sr + Ag)/P atomic ratios of pure and 2%, 5%, 8%, 11% Ag doped particles were 1.74, 1.54, 1.70, 1.74 and 1.66, respectively. The dielectric constant values of pure strontium apatite particles were about 3 at 1 kHz and changed between about 2 to about 5 with Ag doping. The alternative conductivity of samples was increased with increasing frequency. The synthesized nano-strontium apatite particles can be used in orthopedic and dental applications as implant material. (C) 2020 Elsevier B.V. All rights reserved.
15th International Conference on Molecular Spectroscopy (ICMS) - From Molecules to Molecular Materials, Biological Molecular Systems and Nanostructures -- SEP 15-19, 2019 -- Wojanow, POLAND
Keywords: Hydroxyapatite; Strontium apatite; Silver; Nanomaterial; Dielectrical properties; Hydrothermal method